Effect of Robusta coffee beans ointment on full thickness wound healing - Yorinta Putri Kenisa; Istiati Istiati; Wisnu Setyari J (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Traumatic lesions, whether chemical, physical, or thermal in nature, are among the most common lesion in the mouth. Wound healing is essential for the maintenance of normal structure, function, and survival of organisms. Experiments of Robusta coffee powder on rat-induced alloxan incision wound, clinically demonstrated similar healing rate with the povidone iodine 10%. No studies that look directly the effect of coffee extract in ointment form when viewed in terms of histopathology. Robusta coffee bean (Coffea canephora) consists of chlorogenic acid (CGA) and caffeic acid which are belived to act as antioxidant and take part in wound healing process. Purpose: The aim of this study was to identify the enhancement of healing process of full-thickness skin wound after Robusta coffee beans extract ointment application. Methods: Sample consisted of 20 Cavia cabaya treated with full-thickness with wounds and was given Robusta coffee beans extract ointment concentration range of 22.5%, 45%, and 90% except the control group which was given ointment base material. Animals were then harvested on the fourth day and made for histopathological preparations. Data were calculated and compared by one-way ANOVA test and LSD test. Results: The study showed that Robusta coffee bean extract ointment can increase the number of lymphocytes, plasma cells, macrophages, fibroblasts, and blood vessels by the presence of chlorogenic acid (CGA) and Caffeic acid. Conclusion: In conclusion Robusta coffee bean extract ointment enhance the healing process of fullthickness skin wound of Cavia cabaya.Latar belakang: Lesi traumatik, baik akibat rangsang kimia, fisik, atau termal, merupakan lesi yang paling umum terjadi di dalam rongga mulut. Penyembuhan luka yang terjadi ini penting untuk pemeliharaan struktur normal, fungsi, dan kelangsungan hidup organisme. Percobaan pemberian bubuk kopi Robusta terhadap luka sayatan pada tikus yang diinduksi aloksan, secara klinis menunjukkan tingkat penyembuhan yang sama dengan povidone iodine 10%. Namun belum ada penelitian yang melihat secara langsung pengaruh ekstrak kopi dalam bentuk salep bila dilihat dari segi histopatologi. Biji kopi Robusta (Coffea canephora) terdiri dari chlorogenic acid (CGA) dan caffeic acid yang dipercaya berperan sebagai antioksidan dan mengambil bagian dalam proses penyembuhan luka. Tujuan: Tujuan penelitian ini adalah untuk mengidentifikasi peningkatan proses penyembuhan luka full-thickness pada kulit setelah pengaplikasian salep ekstrak biji kopi Robusta. Metode: Sampel terdiri dari 20 Cavia cabaya yang diberi perlakuan berupa luka sayat full-thickness pada kulit punggung dan diberi salep ekstrak biji kopi Robusta dengan beberapa konsentrasi, yaitu 22,5%, 45%, dan 90%, sedangkan kelompok kontrol hanya diberi bahan dasar salep. Binatang coba kemudian dieksekusi pada hari keempat dan dibuat sediaan histopatologinya. Data dihitung dan dibandingkan dengan uji One-Way ANOVA dan uji LSD. Hasil: Hasil penelitian menunjukkan bahwa salep ekstrak biji kopi Robusta dapat meningkatkan jumlah limfosit, sel plasma, makrofag, fibroblas, dan pembuluh darah yang dipengaruhi oleh chlorogenic acid (CGA) dan caffeic acid. Kesimpulan: Disimpulkan bahwa salep ekstrak biji kopi Robusta memiliki efek dapat meningkatkan proses penyembuhan luka full-thickness pada kulit Cavia cabaya.